Автоматизація споруди захищеного ґрунту як електротехнічного комплексу з функцією моніторингу - Волошина, А. А.; Кашкарьов, А. О. (Енергетика і автоматика, 2017)
GREENHOUSE AUTOMATION AS ELECTROTECHNICAL COMPLEX WITH FUNCTION DIAGNOSIS BASED ON ANALYSIS TRANSFER FUNCTION OBSERVED PARAMETERSA. Voloshina, A. Kashkarov The objective of the article - a decrease in the cost of automation of technological processes of plant greenhouses, monitoring of its realization and implementation of actions and means to improve its indexes on the basis electrotechnology on farm businesses by increasing the information content of sensors.The object of research - technological process of plant in greenhouses farm enterprises as electricalcomplex control object.In order to provide raw material processing industries need to restore the national plant of Ukraine. In the article the subject of research. Were accentuated the greenhouse in a small business. These causes, which stop the intensive development of the of plant and introduce elektrotehnologіy in greenhouses these enterprises.The concept of remote monitoring technology of plant process. This will lower the cost price support of  technological process. Simplify implementation of monitoring functions and lower the cost of consulting services. There is a possibility of realization of passive and active experiments on introduction of experimental electrotechnology in the conditions of small enterprises under the supervision of qualified personnel.The novelty of the work consists in the development of remote monitoring techniques. The technique consists in gaining dependencies universal indexes of plant response to the deviation of controlled process parameters. This ensures the observability of the greenhouse.A special feature realization of such approach is the distribution enterprises that make up the target audience of end users. They are characterized by a low level of competence of various external and internal factors of the implementation of technological process. In this connection there is need to develop means and measures to normalize the input data. Normalization of data and modern realities require rapid accumulation of the knowledge base for the formation of a decision support system. Algorithms for such a system are known and used.According to the accepted concept of achievement proposed monitoring of the dynamic characteristics at each stage of the process. This will make the right managerial and technological solutions. The advantage of this approach is that the resulting single equation allows switch to other types of mathematical descriptions. The data may analyze the mathematical tools of harmonic analysis.These article a proposal technically and economically not possible to implement in a single farm enterprise management system. Therefore, it is advisable to pay attention to the remote monitoring and consultation. The introduction of a remote monitoring function allows the accumulation of knowledge and multi-user work with the information.